THE CONCEPT OF SETTING FEES FOR OFFICIALS MAKING LAND DEEDS (PPAT) EQUITABLE FOR OFFICIALS MAKING LAND DEEDS (PPAT) IN INDONESIA - Dewi Amrom Musta’idah; Abdul Madjid; Endang Sri Kawuryan (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
Abstract: This study discusses the juridical study of the upper limits on fees for making land dees (PPAT) from the perspective of making land deeds (PPAT) as public officials. This study is a normative study with a conceptual approach and statutory approach. The data collection technique was carried out by means of a literature study. The results of the analysis result showed that the regulation regarding the upper limits for PPAT fees in f the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 33 of 2021 does not yet reflect the principle of justice for PPATs as public officials and the concept of regulation regarding PPAT fees which can create justice and legal certainty by equalizing fees like other public officials.